2019
DOI: 10.1016/j.fbp.2019.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Design of biomass value chains that are synergistic with the food–energy–water nexus: Strategies and opportunities

Abstract: Humanity's future sustainable supply of energy, fuels and materials is aiming towards renewable sources such as biomass. Several studies on biomass value chains (BVCs) have demonstrated the feasibility of biomass in replacing fossil fuels. However, many of the activities along the chain can disrupt the food-energy-water (FEW) nexus given that these resource systems have been ever more interlinked due to increased global population and urbanisation. Essentially, the design of BVCs has to integrate the systems-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 86 publications
0
23
0
Order By: Relevance
“…Actually, the process of coal mining, processing, and refining needs plenty of water, as well as hydropower generation [56]. In addition, biomass resources mainly come from the organic matter of animals and plants [57,58]. From the perspective of the food subsystem, the main resources to be invested in food production and consumption include water, energy, chemical fertilizers, plastic film for farm use and cultivated land, etc.…”
Section: Nexus Analysis Of Indexmentioning
confidence: 99%
“…Actually, the process of coal mining, processing, and refining needs plenty of water, as well as hydropower generation [56]. In addition, biomass resources mainly come from the organic matter of animals and plants [57,58]. From the perspective of the food subsystem, the main resources to be invested in food production and consumption include water, energy, chemical fertilizers, plastic film for farm use and cultivated land, etc.…”
Section: Nexus Analysis Of Indexmentioning
confidence: 99%
“…By identifying the optimal conditions, the scale-up of this technology could be investigated in terms of its economic and environmental impacts (Doliente and Samsatli, 2019; J o u r n a l P r e -p r o o f al., 2019). Accounting for these impacts is paramount in the commercial implementation of waste technologies and their sustainable integration into biomass supply chains in both developed and developing countries (Doliente et al, 2020;Tapia et al, 2019).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…The optimal biochar product was analyzed using scanning electron microscopy (SEM) with energy dispersive x-ray (EDX), x-ray fluorescence (XRF), Brunauer–Emmett–Teller (BET), and cyclic voltammetry (CV). By identifying the optimal conditions, the scale-up of this technology could be investigated in terms of its economic and environmental impacts ( Doliente and Samsatli, 2019 ; Tapia et al., 2019 ). Accounting for these impacts is paramount in the commercial implementation of waste valorization technologies and their sustainable integration into biomass supply chains in both developed and developing countries ( Doliente et al., 2020 ; Tapia et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 134 peer-reviewed studies were found through the systematic literature search. However, studies that focused on agricultural residues were excluded [478][479][480] , land use mapping [481][482][483][484] , stakeholders' perspectives and decision making [485][486][487][488] , farmland services (e.g., dairy and poultry) [489][490][491] and review style studies [492][493][494][495] . Thus, in total only 59 studies fell within the scope of the study.…”
Section: Observations Of Synergies and Trade-offs Of Land Use For Bio...mentioning
confidence: 99%
“…There are considerably more tradeoffs than synergies between the impacts of land use for dedicated energy crops on GHG emission reduction (SDG 13) and zero hunger (SDG 2). Literature has highlighted that food security risks increase when land dedicated to food production is limited by the production of dedicated energy crops 46,495,510,513,518,[528][529][530] . Land competition can negatively affect agricultural production and food supply, and lead to increases in food prices 37,511 .…”
Section: Rq3: What Are the Synergies And Trade-offs Between Environme...mentioning
confidence: 99%